Ten modifiers of BRCA1 penetrance validated in a Norwegian series - Heramb, Cecilie (Hered Cancer Clin Pract, 2015)
BACKGROUND: Common genetic variants have been shown to modify BRCA1 penetrance. The aim of this study was to validate these reports in a special cohort of Norwegian BRCA1 mutation carriers that were selected for their extreme age of onset of disease. METHODS: The ten variants rs13387042, rs3803662, rs8170, rs9397435, rs700518, rs10046, rs3834129, rs1045485, rs2363956 and rs16942 were selected to be tested on samples from our biobank. We selected female BRCA1 mutation carriers having had a diagnosis of breast or ovarian cancer below 40 years of age (young cancer group, N = 40), and mutation carriers having had neither breast nor ovarian cancer above 60 years of age (i.e., old no cancer group, N = 38). Relative risks and odd ratios of belonging to the young cancer versus old no cancer groups were calculated as a function of having or not having the SNPs in question. RESULTS: Five of the ten variants were found to be significantly associated with early onset cancer. Some of the variation between our results and those previously reported may be ascribed to stochastic effects in our limited number of patient studies, and/or genetic drift in linkage disequilibrium in the genetically isolated Norwegian population. This is in accordance with the understanding that the SNPs are markers in linkage disequilibrium with their respective disease-causing genetic variants, and that this may vary between different populations. CONCLUSIONS: The results confirmed associations previously reported, with the notion that the degree of association may differ between other populations, which must be considered when discussing the clinical use of the associations described. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13053-015-0035-0) contains supplementary material, which is available to authorized users.